Nitric oxide generated by the rice blast fungus Magnaporthe oryzae drives plant infection. Issue 1 (16th October 2012) - Samalova, Marketa; Johnson, Jasper; Illes, Mary; Kelly, Steven; Fricker, Mark; Gurr, Sarah
Summary: Plant‐derived nitric oxide (NO) triggers defence, priming the onset of the hypersensitive response and restricting pathogen ingress during incompatibility. However, little is known about the role of pathogen‐produced NO during pre‐infection development and infection. We sought evidence for NO production by the rice blast fungus during early infection. NO production was measured using fluorescence of DAR‐4M and the role of NO assessed using NO scavengers. The synthesis of NO was investigated by targeted knockout of genes potentially involved in NO synthesis, including nitric oxide synthase‐like genes ( NOL2 and NOL3 ) and nitrate ( NIA1) and nitrite reductase ( NII1 ), generating single and double Δnia1Δnii1, Δnia1Δnol3, and Δnol2Δnol3 mutants. We demonstrate that Magnaporthe oryzae generates NO during germination and in early development. Removal of NO delays germling development and reduces disease lesion numbers. NO is not generated by the candidate proteins tested, nor by other arginine‐dependent NO systems, by polyamine oxidase activity or non‐enzymatically by low pH. Furthermore, we show that, while NIA1 and NII1 are essential for nitrate assimilation, NIA1, NII1, NOL2 and NOL3 are all dispensable for pathogenicity. Development of M. oryzae and initiation of infection are critically dependent on fungal NO synthesis, but its mode of generation remains obscure.